Design synthesis and biological evaluation of new antiplasmodial compounds related to ellagic acid - Brasil, Bernardo Santos (2018)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017